Model Pembelajaran Two Stay Two Stray (TSTS) Efektif Meningkatkan Motivasi, Partisipasi, dan Hasil Belajar IPS Peserta Didik Sekolah Dasar - Maryati Maryati; Tarto Tarto (Proceedings Series on Social Sciences & Humanities, 2022)
This research is a classroom action research (classroom action research). The subjects of this study were the fifth grade students of SDN Senepo Purworejo, totaling 23 students. Techniques Data collection is done by observation and tests. The data analysis technique used quantitative descriptive techniques with percentages. The results of the study concluded that 1) the use of the two stray two stay scramble method can increase the learning motivation in the pre-cycle of 60.87%, increased to 69.57% at the first cycle, and 91.31% at the second cycle. 2) The use of the two stray two stay scramble method can increase the learning participation in the pre-cycle of 65.22%. increased to 73.92% at the first cycle, and increased to 86.92 at the second cycle. 3) The use of the two stray two stay method can improve the learning outcomes students in the pre-cycle with an average value of 70 .65 or 11 students (47.83%) who achieved the KKM score 72, in the first cycle it became 73.65 or 15 students (65.22%), and in the second cycle with an average score of 75.91 or 19 students (82.91% achieved the KKM score).